Temporal Bacterial Community Diversity in the Nicotiana tabacum Rhizosphere Over Years of Continuous Monocropping - Yan, Lang; Zhang, Wenyou; Duan, Wangjun; Zhang, Yizheng; Zheng, Wen; Lai, Xianjun (Frontiers in Microbiology, 2021)
Long-term continuous monocropping negatively influences the physicochemical and biological characteristics of cultivated soil, especially for the economically important crop of flue-cured tobacco that is intolerant to continuous monocropping. The underlying mechanism of soil sickness under continuous monoculture and the temporal dynamic changes over the tobacco life cycle among different monoculture time spans remain poorly characterized. In this study, high-throughput sequencing targeting the 16S rRNA gene phylogenetic marker was performed on 60 soil samples of rhizosphere soil from flue‐cured tobacco in the replanting, growth and harvest period across 5, 10 and 20 years of a continuous monocropping system. Bacterial community diversity decreased with the increase in duration of continuous monocropping, and the rhizosphere microbiota was highly dynamic in the harvest period. The random forests algorithm identified 17 taxa as biomarkers and a model was established to correlate root microbiota with continuous monocropping time of flue-cured tobacco. Molecular ecological network analysis elaborated the differences and interactions in bacterial co-occurrence patterns under different monocropping systems. The co-occurrence microbial network was larger in size but there were fewer interactions among microbial communities with the increase in continuous monocropping duration. These results provide insights into the changes of flue‐cured tobacco root microbiome diversity in response to continuous monocropping and suggest a model for successional dynamics of the root-associated microbiota over continuous monocropping time and development stage. This study may help elucidate the theoretical basis underlying obstacles to continuous monocropping and could contribute to improving guidance for tobacco production.